STUDENTS’ LOW INTEREST IN LEARNING ENGLISH DESPITE THE USE OF ACTIVE LEARNING STRATEGIES IN JUNIOR HIGH SCHOOL - Mendrofa, Destri Filinia; Gea, Joel Kristiawan; Lase, Arosama; Buulolo, Merihati; Telaumbanua, Icha Mulyanti; Telaumbanua, Yasminar Amaerita (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2026)
Low student interest in English as a Foreign Language (EFL) remains a persistent problem in junior high schools in Indonesia despite the implementation of active learning strategies such as discovery-based learning, collaborative learning, and Project-Based Learning (PjBL). This study aims to analyze the factors that contribute to low student interest in learning English despite the use of active learning strategies. Using a descriptive qualitative design, this study involved 24 seventh-grade students and two English teachers at SMP Negeri 1 Hiliduho. Data were collected through questionnaires, semi-structured interviews, and classroom observations, and analyzed using thematic analysis with data triangulation. The results showed that 41.7% of students showed low interest in learning, influenced by internal factors such as lack of confidence, fear of making mistakes, and limited vocabulary, as well as external factors including inadequate instructional guidance and ineffective group work management. These findings highlight the importance of integrating affective support and instructional scaffolding into active learning strategies to increase students' interest in learning English as a Foreign Language (EFL).ABSTRAKMinat siswa yang rendah terhadap Bahasa Inggris sebagai Bahasa Asing (EFL) tetap menjadi masalah yang persisten di sekolah menengah pertama di Indonesia meskipun telah diterapkan strategi pembelajaran aktif seperti pembelajaran berbasis penemuan, pembelajaran kolaboratif, dan Pembelajaran Berbasis Proyek (PjBL). Penelitian ini bertujuan untuk menganalisis faktor-faktor yang berkontribusi terhadap rendahnya minat siswa dalam belajar Bahasa Inggris meskipun telah menggunakan strategi pembelajaran aktif. Menggunakan desain kualitatif deskriptif, penelitian ini melibatkan 24 siswa kelas VII dan dua guru Bahasa Inggris di SMP Negeri 1 Hiliduho. Data dikumpulkan melalui kuesioner, wawancara semi-terstruktur, dan observasi kelas, serta dianalisis menggunakan analisis tematik dengan triangulasi data. Hasil penelitian menunjukkan bahwa 41,7% siswa menunjukkan minat belajar yang rendah, dipengaruhi oleh faktor internal seperti kurangnya kepercayaan diri, rasa takut membuat kesalahan, dan kosakata yang terbatas, serta faktor eksternal termasuk bimbingan instruksional yang tidak memadai dan manajemen kerja kelompok yang tidak efektif. Temuan ini menyoroti pentingnya mengintegrasikan dukungan afektif dan scaffolding instruksional ke dalam strategi pembelajaran aktif untuk meningkatkan minat siswa dalam belajar Bahasa Inggris sebagai Bahasa Asing (EFL).